2020
DOI: 10.1038/s41598-020-62519-5
|View full text |Cite
|
Sign up to set email alerts
|

Inter-task transfer of prism adaptation depends on exposed task mastery

Abstract: The sensorimotor system sets up plastic alterations to face new demands. Terms such as adaptation and learning are broadly used to describe a variety of processes underlying this aptitude. The mechanisms whereby transformations acquired to face a perturbation generalize to other situations or stay context-dependent remain weakly understood. Here, we compared the performance of hand pointing vs throwing to visual targets while facing an optical shift of the visual field (prismatic deviation). We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…The results showed that after-effects tended to decrease across repetitions of trials, demonstrating that throwing after-effects were labile. This is reminiscent with our previous investigations of after-effects during throwing prism exposure (Fleury et al, 2020) and with previous studies using throwing during PA procedure (Martin et al, 1996a;Fernández-Ruiz et al, 2000). Patient studies previously demonstrated the crucial role of the cerebellum in PA, both in error reduction and after-effects (e.g., Weiner et al, 1983;Pisella et al, 2005), by using pointing tasks.…”
Section: Stimulation Effects During Exposure and Throwing After-effectssupporting
confidence: 80%
See 3 more Smart Citations
“…The results showed that after-effects tended to decrease across repetitions of trials, demonstrating that throwing after-effects were labile. This is reminiscent with our previous investigations of after-effects during throwing prism exposure (Fleury et al, 2020) and with previous studies using throwing during PA procedure (Martin et al, 1996a;Fernández-Ruiz et al, 2000). Patient studies previously demonstrated the crucial role of the cerebellum in PA, both in error reduction and after-effects (e.g., Weiner et al, 1983;Pisella et al, 2005), by using pointing tasks.…”
Section: Stimulation Effects During Exposure and Throwing After-effectssupporting
confidence: 80%
“…During pre-tests and post-tests, we computed terminal errors by grouping the right and central targets as a previous study using the same procedures reported no difference between targets (Fleury et al, 2020(Fleury et al, , 2021. We conducted a specific analysis of pointing trajectories for right and central targets as the initial directions and the length of trajectories were intrinsically dependent on the target position.…”
Section: Pointing Kinematics Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Three patients with corpus callosum disorders (MS, MM, and AM) and 16 healthy individuals participated in the study. The number of healthy participants reflect the sample size used in similar studies ( Wang and Sainburg, 2003 ; Morton and Bastian, 2004 ; Perez et al, 2007a ; O’Shea et al, 2014 ; Lefumat et al, 2015 ; Leclere et al, 2019 ; Striemer et al, 2019 ; Bao et al, 2020 ; Fleury et al, 2020 ; Renault et al, 2020 ). Patient MS was a 50-year-old left-handed female with recently acquired lesions of the body of the corpus callosum, sparing the splenium and the genu.…”
Section: Methodsmentioning
confidence: 99%